2016
DOI: 10.1155/2016/6838976
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Recent Developments for Detection of Diabetic Retinopathy

Abstract: Diabetic retinopathy is caused by the retinal micro vasculature which may be formed as a result of diabetes mellitus. Blindness may appear as a result of unchecked and severe cases of diabetic retinopathy. Manual inspection of fundus images to check morphological changes in microaneurysms, exudates, blood vessels, hemorrhages, and macula is a very time-consuming and tedious work. It can be made easily with the help of computer-aided system and intervariability for the observer. In this paper, several technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 91 publications
0
57
0
Order By: Relevance
“…An epidemiological survey showed that the prevalence rate of DR in China has increased on a yearly basis [2]. DR is caused by alterations in the retinal micro vasculature in diabetic patients, and retina neovascularization is one of the most significant clinical properties of proliferative diabetic retinopathy (PDR) [3]. Therefore, anti-neovascularization strategies are the only effective form of therapy for PDR.…”
Section: Introductionmentioning
confidence: 99%
“…An epidemiological survey showed that the prevalence rate of DR in China has increased on a yearly basis [2]. DR is caused by alterations in the retinal micro vasculature in diabetic patients, and retina neovascularization is one of the most significant clinical properties of proliferative diabetic retinopathy (PDR) [3]. Therefore, anti-neovascularization strategies are the only effective form of therapy for PDR.…”
Section: Introductionmentioning
confidence: 99%
“…In computer aided diagnosis for retinal diseases, the precise retinal blood vessel segmentation process is compulsory such as Amin, Sharif, and Yasmin (), Amin, Sharif, Yasmin, Ali, and Fernandes (), Qureshi, Sharif, Yasmin, Raza, and Javed (), Shabbir, Sharif, Nisar, Yasmin, and Fernandes (), Akbar, Akram, Sharif, Tariq, & ullah Yasin (),Akbar, Akram, Sharif, Tariq, and Khan (), and Akbar, Akram, Sharif, Tariq, and ullah Yasin (). The article explains an analysis of segmentation methods for retinal vessel through which the readers can understand the existing literature and provides a framework of existing research which will provide a foundation for future research and publicly available databases for different users in research.…”
Section: Resultsmentioning
confidence: 99%
“…Other restorative difficulties most often result in this sort of glaucoma (Giaconi et al, 2016 (Akbar, Akram, Sharif, Tariq, & Yasin, 2018;Amin, Sharif, Yasmin, Ali, & Fernandes, 2017;Amin et al, 2016;Station, 2007).…”
Section: Secondary Glaucomamentioning
confidence: 99%
“…The factors considered to detect glaucoma include neuro‐retinal rim notching, peripapillary atrophy, RNFL, neuroretinal rim thinning, the optic cup‐to‐disc ratio (CDR), disc haemorrhage and inter‐eye asymmetry defect. The persons suffering from hyperlipidemia, the chances of glaucoma and diabetic retinopathy are enhanced (Akbar, Akram, Sharif, Tariq, & Yasin, ; Amin, Sharif, Yasmin, Ali, & Fernandes, ; Amin et al, ; Station, ).…”
Section: Introductionmentioning
confidence: 99%